2023
DOI: 10.3390/pharmaceutics15051523
|View full text |Cite
|
Sign up to set email alerts
|

High Biocompatibility, MRI Enhancement, and Dual Chemo- and Thermal-Therapy of Curcumin-Encapsulated Alginate/Fe3O4 Nanoparticles

Abstract: (1) Background: Magnetite (Fe3O4) nanoparticles have great potential for biomedical applications, including hyperthermia and magnetic resonance imaging. In this study, we aimed to identify the biological activity of nanoconjugates composed of superparamagnetic Fe3O4 nanoparticles coated with alginate and curcumin (Fe3O4/Cur@ALG) in cancer cells. (2) Methods: The nanoparticles were evaluated for the biocompatibility and toxicity on mice. The MRI enhancement and hyperthermia capacities of Fe3O4/Cur@ALG were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…This approach aims to simplify the composition of the multifunctional nanosystem while retaining the required properties. Many inorganic nanosystems have both imaging and treatment feasibility, such as SIONs used for MRI and thermal therapy, 168 AuNPs for CT and radiation therapy, 169 gold nanorods for CT contrast enhancement, and PTT. 170 …”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…This approach aims to simplify the composition of the multifunctional nanosystem while retaining the required properties. Many inorganic nanosystems have both imaging and treatment feasibility, such as SIONs used for MRI and thermal therapy, 168 AuNPs for CT and radiation therapy, 169 gold nanorods for CT contrast enhancement, and PTT. 170 …”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…A variety of techniques have been used to assess biocompatibility in vitro, including trypan blue exclusion, MTT, and LDH cytotoxicity assays. Additionally, methods like confocal microscopy and flow cytometry allow for a thorough examination of the interactions between cells and Fe NPs [177]. A study has revealed that optimally synthesized Fe NPs typically exhibit lower toxicity and better biocompatibility [178].…”
Section: In Vitro and In Vivo Studies On The Biocompatibility And Tox...mentioning
confidence: 99%
“…Magnetite nanoparticles (Fe 3 O 4 NPs) have attracted considerable attention in many application areas, including environmental treatment [ 1 , 2 , 3 ], food analysis [ 4 , 5 , 6 ], biosensors [ 7 , 8 ], protein immobilization [ 9 ], targeted drug delivery [ 10 , 11 , 12 , 13 , 14 ], separation [ 15 , 16 , 17 ], magnetic resonance imaging (MRI) [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], magnetofection [ 28 , 29 ], tissue engineering [ 30 ], and hyperthermia [ 31 , 32 ]. In particular, their good biocompatibility, as verified by the U.S. Food and Drug Administration [ 33 ], facilitates their commercialization.…”
Section: Introductionmentioning
confidence: 99%